2013
DOI: 10.1556/eujmi.3.2013.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm-related cutaneous larva migrans in patients living in an endemic community in Brazil: Immunological patterns before and after ivermectin treatment

Abstract: Hookworm-related cutaneous larva migrans (Hr-CLM) is caused by animal hookworm larvae migrating in the human epidermis where they elicit an inflammatory response. This study describes the immunological profile in Hr-CLM patients.In 77 Hr-CLM patients from Manaus, Brazil, peripheral eosinophils were counted, and serum concentrations of total immunoglobulin E (IgE) and selected cytokines were determined by ELISA before and after treatment with ivermectin. Controls included patients' household members (endemic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These modifications were applied in patients with cutaneous larva migrans, scabies, and tungiasis. 52,53,[93][94][95] Improving the awareness of the existence of child-specific HRQoL instruments, such as CDLQI, Teenager's Quality of Life, and Skindex-Teen is recommended. 96,97 Similarly, to other medical specialties, in dermatology, HRQoL can be assessed by using both disease-specific and generic measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications were applied in patients with cutaneous larva migrans, scabies, and tungiasis. 52,53,[93][94][95] Improving the awareness of the existence of child-specific HRQoL instruments, such as CDLQI, Teenager's Quality of Life, and Skindex-Teen is recommended. 96,97 Similarly, to other medical specialties, in dermatology, HRQoL can be assessed by using both disease-specific and generic measures.…”
Section: Discussionmentioning
confidence: 99%
“…The articles by Barbieri and Gelfand (2019 74 and 2019 73 ) used the same dataset and therefore considered one study. The articles by Schuster et al 2011 94 and Shimogowara et al (2013 95 ) used the same dataset and therefore considered one study. † The article by Abbas et al (2015 25 ) used 3 different disease, symptom and body part specifications; therefore, the total number of disease, symptom, and body part specifications is 25 that have been used in overall 30 studies.…”
Section: Measurement Properties Of Dlqi Modifications (Terwee Criteria)mentioning
confidence: 99%
“…Factors that cause vesiculobullous lesions and multiple lesions in CLM are still unknown. Shimogawara et al [13] showed that there were increased levels of several cytokines, such as interleukin (IL)-4, IL-5, IL-6, and IL-10 in the peripheral circulation of CLM patients. The activation of the T helper-2 (Th2) cell leads to an increase in IL-5 level that causes eosinophil withdrawal [1] from the bone marrow to the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…We performed antibody screening using an antiparasite test (SRL Inc., Tokyo, Japan). administration [10]. IL-5 level decreased gradually but the IL-18 and IL-13 directly corresponding to the recurrence and treatment.…”
Section: Introductionmentioning
confidence: 89%